THE RELATIONSHIP BETWEEN MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PRODUCTIVITY AT (PT RIFAN FINANCINDO BERJANGKA JAKARTA) - Macau , Marselus; Anggraini , Nenny; Malau, Melinda (Fundamental Management Journal, 2021)
“PT Rifan Financindo Futures (RBF) is an investor liaison company with the Jakarta Futures Exchange (BBJ) with more than 20 years of experience in the Commodity Futures Trading Industry and is the largest brokerage company by occupying the number one position of the ten most active brokerage companies from PT Kliring Berjangka Indonesia (Persero). The Company is committed to carrying out regular, fair, effective and transparent futures trading as stipulated in the law in the Futures Trading sector to provide legal certainty for all parties in Futures Trading activities in Indonesia.). In this study, the issues to be discussed is how is the relationship between motivation and work discipline on employee productivity at PT Rifan Financindo Berjangka (RFB). The research was conducted at the PT Rifan Financindo Berjangka (RFB). The purpose of this study was to determine the relationship of motivation and work diciplinediscipline on employee productivity at At PT Rifan Financindo Berjangka (RFB). This research is a survey research with a quantitative approach. The sample of this research is the employees of PT Rifan Financindo Berjangka Jakarta, which found 50 employees with the sampling technique is Non Probability Sampling. The result of this study was indicated that 1) there is a positive and significant the relationship of motivation and work dicipline At PT Rifan Financindo Berjangka (RFB). It is shown by Rank Sperman (0,576), 2) there is a positiveand significant relationship between work discipline and employee productivity at PT Rifan Financindo Berjangka (RFB). It is shown by (0,732)” Keyword : Motivation; Work discipline; Employee productivity